HUBUNGAN PAPARAN WHOLE BODY VIBRATION DAN MASA KERJA DENGAN PENURUNAN KETAJAMAN PENGLIHATAN PENGEMUDI PADA PO NIKKO PUTRA DI KOTA YOGYAKARTA - Wibowo, Andi; Hariyono, Widodo; Septiasih, Kentari (Universitas Ahmad Dahlan, 2011)
PO Nikko Putra is a bus company which serves Yogyakarta - Tempel route. The condition of bus machine which have old and lack of maintenance will cause high exposure a whole body vibration felt by the driver. The long exposure whole body vibration will generate health troubles, one of them degradation of visus. This research is aimed to know the correlation whole body vibration and working time with visus degradation of the driver. This research is conducted observasionally with cross sectional design. Research population are 55 people and the sample obtained is 26 people which meet the inclusion criterion. Exopusure whole body vibration suffered by driver is 1.257 m /s presence during 11 hours in one day, according to ISO 2631 included in category exopusure limit. The result of correlation analysis on Pearson coefficient of exposure whole body vibration and visus for right eye with p 0.981 and the left eye p 0.592, hence Ho is accepted because the p value > 0.05. Whereas, the analysis on the working time with degradation of right eye visus with p 0.709 and the left eye with p 0.990, hence Ho is accepted because probability value > 0.05. This research conclude that there is no correlation whole body vibration and working time with degradation of visus that the driver.Keyword: driver, whole body vibration and visus